The Stress Hormone Corticosterone Increases Synaptic α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid (AMPA) Receptors via Serum- and Glucocorticoid-inducible Kinase (SGK) Regulation of the GDI-Rab4 Complex - Liu, Wenhua (American Society for Biochemistry and Molecular Biology, 2010)
Corticosterone, the major stress hormone, plays an important role in regulating neuronal functions of the limbic system, although the cellular targets and molecular mechanisms of corticosteroid signaling are largely unknown. Here we show that a short treatment of corticosterone significantly increases α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR)-mediated synaptic transmission and AMPAR membrane trafficking in pyramidal neurons of prefrontal cortex, a key region involved in cognition and emotion. This enhancing effect of corticosterone is through a mechanism dependent on Rab4, the small GTPase-controlling receptor recycling between early endosome and plasma membrane. Guanosine nucleotide dissociation inhibitor (GDI), which regulates the cycle of Rab proteins between membrane and cytosol, forms an increased complex with Rab4 after corticosterone treatment. Corticosterone also triggers an increased GDI phosphorylation at Ser-213 by the serum- and glucocorticoid-inducible kinase (SGK). Moreover, AMPAR synaptic currents and surface expression and their regulation by corticosterone are altered by mutating Ser-213 on GDI. These results suggest that corticosterone, via SGK phosphorylation of GDI at Ser-213, increases the formation of GDI-Rab4 complex, facilitating the functional cycle of Rab4 and Rab4-mediated recycling of AMPARs to the synaptic membrane. It provides a potential mechanism underlying the role of corticosteroid stress hormone in up-regulating excitatory synaptic efficacy in cortical neurons.